Determinants of Hesitancy Towards COVID-19 Vaccines in State of Kuwait: An Exploratory Internet-Based Survey - Al-Ayyadhi N; Ramadan MM; Al-Tayar E; Al-Mathkouri R; Al-Awadhi S (Dove Medical Press, 2021)
Najla Al-Ayyadhi,1 Marwa Mohsen Ramadan,2 Eman Al-Tayar,3 Radhia Al-Mathkouri,3 Shaimaa Al-Awadhi3 1Public Health Specialist, Directorate of Public Health, Ministry of Health, Kuwait City, State of Kuwait; 2Lecturer of Community Medicine, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 3Public Health Physician, Directorate of Public Health, Ministry of Health, Kuwait City, State of KuwaitCorrespondence: Najla Al-AyyadhiPublic Health Department, Kuwait Ministry of Health, P.O. Box 17782, Khaldeya, Kuwait City, 72458, State of KuwaitTel +965 99644676Email dr.najla1001@hotmail.comBackground: The coronavirus disease 2019 (COVID-19) pandemic has wrought havoc upon healthcare and economic systems worldwide. COVID-19 vaccines considered a beacon of hope for normal life to return. We wished to understand the willingness of people in Kuwait to be vaccinated against COVID-19.Methods: An online, exploratory, cross-sectional study was conducted on 16- 18 January 2021 using a validated structured questionnaire to collect data from adults aged 18 years or older living in Kuwait by applying a "snowball sampling" method.Results: A total of 7274 people received an online link of the survey on their smartphone or computer, and 6943 people enrolled in this study (95.4%). Kuwaiti nationals represented 79.7% of the study cohort, 54.8% were aged ≥ 40 years, and 66.7% were females. Hesitancy against a COVID-19 vaccine was remarkably high (74.3%), with 50.8% not planning to take it and 23.5% not sure about taking it. The overall mean perception score was 3.4 ± 2.8, with 66.8% having a negative attitude towards a COVID-19 vaccine. Multiple logistic regression analysis of the factors affecting the decision to take a COVID-19 vaccine was done. The decision to take a COVID-19 vaccine was significantly positively associated with younger age (OR = 1.219), being male (2.169), having a higher education level (1.362), vaccinated against seasonal influenza previously (2.706), being a non-Kuwaiti (1.329), being a healthcare worker (1.366), and working in the private sector (1.228). Options to encourage future COVID-19 vaccination were more studies showing the vaccine to be safe and efficacious (68.6%), physician recommendation (41.8%), mandatory travel requirements (39.8%), if a family or friend vaccinated (34.9%) and compulsory by government (33.1%) or for employment (29.8%).Conclusion: Our data suggest that considerable vaccine hesitancy persists despite the widespread availability of highly efficacious and safe COVID-19 vaccines.Keywords: COVID-19, vaccine acceptance, vaccine uptake, hesitancy, barriers